2014
DOI: 10.1039/c4lc00578c
|View full text |Cite
|
Sign up to set email alerts
|

DLD pillar shape design for efficient separation of spherical and non-spherical bioparticles

Abstract: Particle sorting methods in microfluidic platforms are gaining momentum for various biomedical applications. Bioparticles are found in different shapes and sizes. However, conventional separation techniques are mainly designed for separation of spherical particles. Thus, there is a need to develop new methods for effective separation of spherical and non-spherical bioparticles for various applications. Deterministic lateral displacement (DLD) microfluidic methods have become popular for high separation resolut… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
96
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 109 publications
(98 citation statements)
references
References 34 publications
1
96
0
Order By: Relevance
“…However, erythrocyte contamination of the product was significant with nearly 4.5% of the input erythrocytes appearing in the product. At the high Reynolds number used in these flows (Re ~ 10), it has recently been reported that erythrocytes, which have a discoid shape, behave in a DLD array as if they have a much larger size than they do at low Reynolds number, an effect not observed for circular posts [32]. Thus more are collected as “large cells” than would otherwise occur.…”
Section: Dld Array Performance For High Volume Separation At High mentioning
confidence: 99%
“…However, erythrocyte contamination of the product was significant with nearly 4.5% of the input erythrocytes appearing in the product. At the high Reynolds number used in these flows (Re ~ 10), it has recently been reported that erythrocytes, which have a discoid shape, behave in a DLD array as if they have a much larger size than they do at low Reynolds number, an effect not observed for circular posts [32]. Thus more are collected as “large cells” than would otherwise occur.…”
Section: Dld Array Performance For High Volume Separation At High mentioning
confidence: 99%
“…A combination of grooves and protrusions in a microfluidic device could successfully separate, 3D spherical particles, red blood cells (2D planar shaped) and rod shaped bacteria. The bacteria investigated in this work were: E. coli (rod-shaped or bacillus), K. pneumoniae (rod shaped), S. epidermidis (spherical or coccus) and Pseudomonas aeruginosa (rod-like or coccobacillus) (55). The final example is the work of Kang et al (56) who presented a method to selectively detect bacteria directly from milliliters of diluted blood in one step.…”
Section: Micro/nanotechnology Diagnostic Innovationsmentioning
confidence: 97%
“…These DLD devices with shaped pillars are found to have smaller critical sizes than circular ones [26]. Ranjan et al [28] validated that protrusions and groove structures substantially affected separation efficiency. In other words, DLD geometric characteristics play an important role in spherical particle separation.…”
Section: B New Formula For Critical Size Estimationmentioning
confidence: 99%
“…Although a variety of pillar shapes in DLD devices have been evaluated experimentally [28], it is yet a rule of thumb in designing and optimizing DLD microfluidic arrays for efficient separation of biological samples. The critical size is of vital importance in DLD.…”
mentioning
confidence: 99%